2022
DOI: 10.1159/000526734
|View full text |Cite
|
Sign up to set email alerts
|

PROX1 Was Associated with LGR5 and Wnt Signaling and Contributed to Poor Prognosis in Gastric Cancer

Abstract: Introduction: We investigated prospero homeobox protein-1 (PROX1) expression in gastric cancer (GC) as a prognostic marker and its relationship with LGR5 and Wnt/β-catenin activity in GC. Methods: A total of 196 cases of patients who underwent GC surgery were retrospectively collected and reviewed. PROX1, LGR5, Wnt3a, and β-catenin expression was evaluated by using immunohistochemistry. The relationship between PROX1 expression and clinicopathological features was also evaluated. Results: The PROX1 low-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…In 2022, Nakazawa et al. ( 51 ) demonstrated that LGR5 expression in intestinal-type gastric cancer indicated poor overall survival (OS) ( 52 ).…”
Section: Altered Wnt Signaling In Gc Cellsmentioning
confidence: 99%
“…In 2022, Nakazawa et al. ( 51 ) demonstrated that LGR5 expression in intestinal-type gastric cancer indicated poor overall survival (OS) ( 52 ).…”
Section: Altered Wnt Signaling In Gc Cellsmentioning
confidence: 99%